Analysis of Antioxidant Compoundson Gedi’s (Abelmoschus manihot L)Leaf Beverages - Nurul Azizah Choiriyah; Ladyamayu Pinasti; Fathimah Fathimah; Inma Yunita Setyorini (Agroindustrial Technology Journal, 2021)
Gedy plants are known as vegetable crops. People in the Bantul area, Yogyakarta use it as a healthy drink. Gedi leaves are rich in various antioxidant compounds, such as flavonoids, polyphenols and vitamin C. This study aimed to choose the processing of dage drinks (gedi leaves) with minimal antioxidant degradation. The analysis used in this study was antioxidant activity (DPPH method), analysis of total flavonoid content, analysis of vitamin C content. The statistical analysis used was the one-way ANOVA test with further tests namely Duncan's Multiple Range Test (DMRT). This study prove that method of processing affects on antioxidant activity and flavonoid content (p <0.05). Juice processing using juicerwas the best way for produce gedi’s leaf beverage